Method for recovering high-purity silicon from crystalline silicon cutting waste
Patent Information
- Application Number
- CN202410901151.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-05
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-07-05
AI Technical Summary
该方法通过强酸去除晶硅废料SiO2包覆层,可以一定程度上回收晶硅切割废料中的高纯硅核;但是流程长,用到的HCl和HF两种酸对环境危害大,难以实现低成本和批量化的高纯硅资源回收
[0024]本发明提供了一种不需要酸的,可以快速消解晶硅切割废料表面SiO2包覆层,进而回收晶硅切割废料内部硅核的方法。具体来说,依据SiO2-CaCO3-Na2CO3三元相图在1400℃的等温截面图进行工艺设计,利用CaCO3和Na2CO3热分解得到的CaO和Na2O,与晶硅切割废料SiO2包覆层的表层反应形成熔融相;同时,碳酸盐分解得到的CO2在熔融相中形成微气泡,CO2微气泡冲击SiO2包覆层的次表层,加速熔融相对SiO2包覆层的消解;随后升高放电等离子烧结炉温度,由于密度差的存在,由晶硅切割废料内部Si核组成的Si熔体与含有晶硅废料表层SiO2分子的氧化物熔融相出现分层,达到回收晶硅切割废料内部硅核的目的;利用CO2微气泡的冲击作用加速熔融相对SiO2包覆层的消解,这是本发明的核心创新点。
Smart Images

Figure CN118877895B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of industrial solid waste resource recycling, and in particular to a method for accelerating the digestion of SiO2 coatings in crystalline silicon cutting waste using CO2 microbubbles and recovering high-purity silicon. Background Technology
[0002] According to a survey released by the International Energy Agency (IEA) at the end of 2023 and the beginning of 2024, the global cumulative installed capacity of solar photovoltaic (PV) power has exceeded 1200 GW. It is estimated that by 2030, the global cumulative installed capacity of solar PV power will exceed 5000 GW; more than 90% of these solar PV cells are crystalline silicon solar cells. The production of crystalline silicon solar cells requires first cutting silicon ingots into silicon wafers. During the cutting process, nearly half of the solar-grade silicon (99.9999% purity) is wasted as crystalline silicon waste. my country generates approximately 1.4 million tons of crystalline silicon cutting waste annually.
[0003] Crystalline silicon waste has an irregular, flake-like morphology with an average particle size smaller than PM2.5. This tiny size can damage the human respiratory and digestive systems, leading to diseases such as asthma, bronchitis, and even esophageal cancer. Besides its environmental harm, the solar-grade silicon cores (99.9999% purity) inside crystalline silicon cutting waste have extremely high recycling value. Therefore, whether considering reducing the environmental hazards of crystalline silicon cutting waste or improving the overall economic benefits of the crystalline silicon solar photovoltaic industry, it is urgent to recycle the solar-grade silicon cores within the waste. However, the high-purity silicon cores in crystalline silicon cutting waste are coated with a SiO2 layer, which accounts for approximately 10% of the waste's mass. The melting point of the SiO2 layer is much higher than that of the Si cores. This hinders the aggregation, recycling, and subsequent application of the Si cores within the waste. To achieve the resource recycling of the high-purity Si within crystalline silicon cutting waste, it is necessary to first remove the SiO2 coating.
[0004] To address the challenge of the SiO2 coating layer on crystalline silicon waste hindering the reuse of internal silicon cores, Chinese invention patent CN111196696 A proposes a method of mixing crystalline silicon cutting waste with fly ash, crushed stone, and sand, pressing it into brick blanks, and then heating it in a tunnel furnace to produce building bricks. During heating, the silicon cores of the crystalline silicon cutting waste oxidize, forming complete SiO2 particles with the surface SiO2 coating layer, which then become the filler material for the building bricks. This method achieves the reuse of crystalline silicon cutting waste; however, the resulting building bricks have low added value and do not realize the high-value utilization of the high-purity silicon within the crystalline silicon waste.
[0005] Chinese invention patent, publication number CN102642835A, proposes a method for preparing silicon ingots through centrifugal sedimentation, solid-phase rinsing, HCl cleaning, ultrapure water rinsing, HF rinsing to remove the SiO2 coating layer, ultrasonic rinsing, drying, and directional solidification. This method removes the SiO2 coating layer from crystalline silicon waste using strong acids, which can recover high-purity silicon cores from crystalline silicon cutting waste to a certain extent; however, the process is lengthy, and the two acids used, HCl and HF, are highly environmentally harmful, making it difficult to achieve low-cost and large-scale high-purity silicon resource recovery.
[0006] In conclusion, it is necessary to study a method for recovering high-purity silicon resources from crystalline silicon waste. Summary of the Invention
[0007] This application is made in view of the above-mentioned issues, and its purpose is to provide a method for recovering high-purity silicon from silicon crystalline cutting waste.
[0008] To achieve the above objectives, this application provides a method for recovering high-purity silicon from silicon crystalline cutting waste. The method utilizes CaO and Na2O obtained from the thermal decomposition of CaCO3 and Na2CO3 to react with the surface layer of the SiO2 coating on the silicon crystalline cutting waste to form a molten phase. Simultaneously, CO2 obtained from the thermal decomposition of carbonates forms microbubbles in the molten phase. These CO2 microbubbles impact the subsurface layer of the SiO2 coating, accelerating the disintegration of the SiO2 coating by the molten phase. Subsequently, the furnace temperature is increased, and the silicon nuclei inside the silicon crystalline cutting waste are recovered as high-purity silicon ingots using density differences. This method is acid-free and offers rapid recovery.
[0009] The first aspect of this application provides a method for recovering high-purity silicon from silicon crystalline cutting waste, comprising the following steps:
[0010] S1, a small amount of carbonate and binder are mixed into the silicon cutting waste powder to obtain a uniform mixture of silicon cutting waste powder, carbonate and binder.
[0011] S2 involves pressing a mixture of silicon cutting waste powder, carbonate powder, and binder into a blank, followed by vacuum drying to remove the binder from the blank, and then performing spark plasma sintering (SPS) in a graphite crucible.
[0012] S3, increase the power of the discharge plasma sintering furnace to melt the sample from S2, and recover the high-purity Si layer from the bottom of the graphite crucible.
[0013] As a further step, the carbonates mentioned in step S1 are Na2CO3 and CaCO3.
[0014] As a further step, the adhesive mentioned in step S1 is at least one of distilled water and anhydrous ethanol.
[0015] As a further step, in step S1, the amount of CaCO3 and Na2CO3 added is selected from the region in the SiO2-CaCO3-Na2CO3 ternary phase diagram that contains only the molten phase and the gas phase, but no solid phase.
[0016] As a further step, in step S1, the different amounts of CaCO3 and Na2CO3 added will result in different amounts of CO2 microbubbles generated in the molten phase, which will affect the rate of SiO2 coating layer digestion.
[0017] Preferably, in step S1, the mass ratio of silicon cutting waste, Na2CO3, CaCO3, and binder is 300-800:10-60:10:4-8.
[0018] As a further step, in step S1, silicon cutting waste powder, Na2CO3 powder, and CaCO3 powder are added simultaneously and mixed in a double cone mixer for 15-25 minutes; then, binder is continuously sprayed from the nozzle of the mixer for 6-15 minutes.
[0019] As a further step, in step S2, when pressing the billet, a pressure of 18-25 MPa is applied to the upper surface of the billet.
[0020] As a further step, in step S2, the sintering atmosphere is an argon atmosphere with an argon flow rate of 100-200 mL / min.
[0021] As a further step, in step S2, the sintering temperature is 1300℃-1450℃, and the holding time is 20-40min.
[0022] As a further step, in step S3, the furnace temperature reaches 1550-1650℃, the melting time is 15-30 min, and the argon flow rate is the same as in step S2.
[0023] The beneficial effects of this invention are:
[0024] This invention provides a method for rapidly dissolving the SiO2 coating layer on the surface of silicon cutting waste without the need for acid, thereby recovering the silicon cores inside the waste. Specifically, the process is designed based on the isothermal cross-section of the SiO2-CaCO3-Na2CO3 ternary phase diagram at 1400℃. CaO and Na2O, obtained from the thermal decomposition of CaCO3 and Na2CO3, react with the surface layer of the SiO2 coating layer of the silicon cutting waste to form a molten phase. Simultaneously, CO2, obtained from the decomposition of carbonates, forms microbubbles in the molten phase. These CO2 microbubbles impact the subsurface layer of the SiO2 coating layer, accelerating the dissolution of the SiO2 coating layer by the molten phase. Subsequently, the temperature of the discharge plasma sintering furnace is increased. Due to the density difference, the Si melt composed of Si cores from the silicon cutting waste separates from the oxide molten phase containing SiO2 molecules from the surface layer, achieving the goal of recovering the silicon cores inside the waste. The core innovation of this invention lies in utilizing the impact of CO2 microbubbles to accelerate the dissolution of the SiO2 coating layer by the molten phase. Attached Figure Description
[0025] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained from these drawings without creative effort.
[0026] Figure 1 This is a schematic diagram of the structure of the crystalline silicon cutting waste, which is a method for recovering high-purity silicon from crystalline silicon cutting waste according to the present invention.
[0027] Figure 2 The present invention provides a method for recovering high-purity silicon from silicon crystalline cutting waste. When designing the mass fractions of silicon crystalline cutting waste, Na2CO3, and CaCO3, the method is based on the isothermal cross-section of the SiO2-CaCO3-Na2CO3 ternary phase diagram at 1400℃, where SiO2 originates from the SiO2 coating layer of the silicon crystalline cutting waste.
[0028] Figure 3 for Figure 2 The percentage by mass of CO2 gas phase released by four representative components at 1400℃ when the reaction reaches equilibrium relative to the total mass of the reactants.
[0029] Figure 4 This is an electron microscope image showing the impact effect of CO2 microbubbles generated by the thermal decomposition of carbonates in the molten phase obtained from the digestion of a method for recovering high-purity silicon from silicon cutting waste according to the present invention, which forms pores.
[0030] Figure 5This is a schematic diagram illustrating how CO2 microbubbles in the CaO-Na2O-SiO2 molten phase obtained from the digestion of a method for recovering high-purity silicon from silicon cutting waste impact the surface of the SiO2 coating layer and accelerate the digestion of the SiO2 coating layer.
[0031] Figure 6 An optical image of the high-purity silicon recovered from a method for recovering high-purity silicon in silicon cutting waste. Detailed Implementation
[0032] The following detailed description, with appropriate reference to the accompanying drawings, discloses an embodiment of a method for recovering high-purity silicon from silicon wafer cutting waste according to this application. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided for the purpose of enabling those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.
[0033] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0034] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0035] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0036] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0037] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0038] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0039] A method for recovering high-purity silicon from silicon wafer cutting waste includes the following steps:
[0040] S1, a small amount of carbonate and binder are mixed into the silicon cutting waste powder to obtain a uniform mixture of silicon cutting waste powder, carbonate and binder.
[0041] In step S2, a mixture of silicon wafer cutting waste powder, carbonate powder, and binder is pressed into a green body and then vacuum-dried to remove the binder. Subsequently, it undergoes spark plasma sintering (SPS) in a graphite crucible. The carbonate decomposes to form metal oxides and releases CO2 gas. The metal oxides react with the surface layer of the SiO2 coating from the silicon wafer cutting waste to form a molten phase. More importantly, the released CO2 forms microbubbles in the molten phase, and the impact effect of these microbubbles further accelerates the disintegration of the SiO2 coating layer by the molten phase.
[0042] The compact is pressed to ensure close and sufficient contact between the SiO2 layer and carbonate powder on the surface of the silicon cutting waste. Only close and sufficient contact can guarantee that the SiO2 and carbonate react according to the pre-designed ratio and generate a molten phase. The generation of the molten phase means the dissolution of the oxide layer on the surface of the silicon cutting waste. The diameter of the compact should be smaller than the inner diameter of the graphite crucible to ensure that the compact can be easily loaded into the graphite crucible. The characteristic of using a spark plasma sintering furnace is rapid heating; in S2, the heating rate is controlled at 200℃ / min~250℃ / min. Because the temperature at which carbonates decompose and release CO2 gas is lower than the temperature at which the molten phase is formed, CO2 gas is generated before the molten phase during the heating process. Using rapidly heating discharge plasma sintering can greatly shorten the time difference between the two nodes of CO2 gas phase generation and molten phase generation. The time difference should be controlled within 3 minutes, with 1-3 minutes being optimal. This ensures that as much CO2 gas phase as possible is generated in the molten phase, forming more CO2 microbubbles. These CO2 microbubbles can then accelerate the dissolution of the SiO2 layer on the surface of the silicon cutting waste by the molten phase.
[0043] In step S3, the power of the spark plasma sintering furnace is further increased to melt the sample obtained in step S2 after the SiO2 coating has been dissolved. Due to the density difference in the melt, stratification occurs between the Si melt composed of Si cores inside the silicon cutting waste and the oxide melt phase containing SiO2 molecules from the surface of the silicon cutting waste. After cooling, the upper part of the graphite crucible is an oxide layer containing the SiO2 coating from the silicon cutting waste, and the lower part of the graphite crucible is the recovered high-purity Si layer.
[0044] In some embodiments, the carbonates mentioned in step S1 are Na2CO3 and CaCO3.
[0045] The use of Na₂CO₃ and CaCO₃ is based on the SiO₂-CaCO₃-Na₂CO₃ ternary phase diagram. Adding only one would increase the temperature required to form the molten phase, significantly increasing the energy consumption of this process and thus reducing its economic efficiency. Furthermore, the decomposition products of Na₂CO₃ and CaCO₃ are Na₂O and CaO, respectively. These two oxides have different basicities (providing O₂ in the molten phase). 2- (The capabilities differ). Furthermore, in regulating the viscosity of the molten phase, Na₂O can simplify the silicon-oxygen tetrahedral structure in the molten phase, reduce the degree of polymerization of the molten phase, thereby reducing viscosity and promoting the stratification of the subsequent oxide molten phase and the silicon melt.
[0046] In some embodiments, the binder in step S1 is at least one of distilled water and anhydrous ethanol. Using distilled water as the binder is beneficial for cost control.
[0047] In some implementations, in step S1, the amount of CaCO3 and Na2CO3 added is selected from the region in the SiO2-CaCO3-Na2CO3 ternary phase diagram that contains only the molten phase and the gas phase, but no solid phase. The components selected from this region mean that the added CaCO3 and Na2CO3 can completely dissolve the SiO2 coating layer on the surface of the silicon crystalline cutting waste into the molten phase.
[0048] Different regions in the SiO2-CaCO3-Na2CO3 ternary phase diagram represent different proportions of calcium carbonate, silicon dioxide, and sodium carbonate, and the products when these proportions reach equilibrium. Selecting a region is essentially choosing a range of proportions. The ternary phase diagram is more intuitive and is a method in the field of chemical reaction thermodynamics for visually describing reaction products, enabling better product control.
[0049] In some implementations, the different amounts of CaCO3 and Na2CO3 added in step S1 will result in different amounts of CO2 microbubbles generated in the molten phase, which will affect the rate of SiO2 coating layer decomposition.
[0050] The amount of microbubbles is controlled by the amount of Na2CO3 added. During heating, carbonates decompose and release CO2, which forms CO2 microbubbles in the molten phase. Theoretically, a faster digestion rate is better; however, as can be seen from the SiO2-CaCO3-Na2CO3 ternary phase diagram, if the amount of Na2CO3 added is too high, the reaction products will appear as a solid phase, hindering the separation of the silicon nucleus from the oxide molten phase during subsequent melting. Therefore, the amounts of CaCO3 and Na2CO3 added should not be too high, with a range of 300-800:10-60:10:4-8.
[0051] In some embodiments, in step S1, the mass ratio of silicon dicing waste, Na2CO3, CaCO3, and binder is 300-800:10-60:10:4-8; if the mass of the SiO2 coating layer accounts for approximately 10% of the silicon dicing waste, then the mass ratio of SiO2, Na2CO3, CaCO3, and binder is 30-80:10-60:10:4-8. The isothermal section of the SiO2-CaCO3-Na2CO3 ternary phase diagram at 1400°C is also described. Figure 2 As can be seen, at 1400℃, the reaction products can contain only molten and gaseous phases but no solid phase. This indicates that the SiO2 coating on the silicon cutting waste is completely dissolved when the reaction reaches equilibrium, which is beneficial for the aggregation of silicon nuclei inside the silicon cutting waste after heating. As for the amount of binder added, too little will lead to insufficient bonding, and the pressed green body is prone to cracking; too much will cause the green body to stick to the mold, which is not conducive to demolding.
[0052] If the above-mentioned components are too large or too small, the reaction products are likely to form a solid phase. The presence of a solid phase is not conducive to the separation of the molten phase from silicon during the melting process. In other words, exceeding this range is not conducive to the recovery of high-purity silicon.
[0053] In some embodiments, the first function of the carbonates mixed in during step S1 is: thermal decomposition at high temperature releases Na₂O and CaO, which react with the SiO₂ layer of silicon wafer cutting waste to form a molten phase. The second function of the carbonates is: the CO₂ released during decomposition forms microbubbles in the molten phase; these microbubbles impact the subsurface layer of the SiO₂ coating layer, accelerating the dissipation of the SiO₂ coating layer by the molten phase, shortening the process time, and reducing energy consumption. The third function of the carbonates is: if added directly in the form of Na₂O and CaO, they would react with the binder to form sodium hydroxide and calcium hydroxide, leading to failure. However, these two carbonates do not react with the binder; after vacuum drying to remove the binder, thermal decomposition releases Na₂O and CaO, thus preventing the failure of Na₂O and CaO.
[0054] In some embodiments, in step S1, the mixing conditions are as follows: first, silicon cutting waste powder, Na2CO3 powder, and CaCO3 powder are added simultaneously and mixed in a double-cone mixer for 15-25 minutes; then, binder is continuously sprayed from the nozzle of the mixer for 6-15 minutes. Using distilled water as the binder can prevent cracking of the green body, ensure low processing costs, and avoid the introduction of impurities. Anhydrous ethanol can also be used as the binder, but it is more expensive and poses a fire hazard during mass production.
[0055] In some embodiments, during step S2, the pressure on the upper surface of the blank is 18-25 MPa when pressing the blank. Below this value, the blank is difficult to densify; above this value, the blank is prone to breakage during demolding.
[0056] In some embodiments, in step S2, the sintering atmosphere is an argon atmosphere with an argon flow rate of 100-200 mL / min. Too high a flow rate will cause excessive temperature fluctuations during the sintering process, which is not conducive to the stability of the sintering process. Too low an argon flow rate will reduce the isolation effect on the outside air, and the silicon core inside the silicon cutting waste will be easily oxidized.
[0057] In some embodiments, in step S2, the sintering temperature is 1300℃-1450℃, and the holding time is 20-40 minutes. If the sintering temperature is too low, the molten phase is difficult to form, the SiO2 coating on the surface of the silicon cutting waste is difficult to dissolve, and the high-purity silicon core recovery fails. If the sintering temperature is too high, it will damage the service life of the discharge plasma sintering furnace and lead to excessive energy consumption. If the holding time is too short, Na2CO3 and CaCO3 cannot be completely decomposed, therefore the SiO2 coating cannot be completely dissolved into the Na2O and CaO obtained from the decomposition into the molten phase; while a long holding time results in high energy consumption.
[0058] In some embodiments, in step S3, after further increasing the power of the discharge plasma sintering furnace, the furnace temperature reaches 1550-1650℃, the melting time is 15-30 min, and the argon flow rate is the same as in step S2. Below 1550℃, the Si melt and the oxide molten phase containing SiO2 molecules have poor fluidity and are difficult to completely separate; above 1650℃, energy consumption is too high. When the melting time is less than 15 min, the Si melt and the oxide molten phase containing SiO2 molecules do not completely separate, resulting in poor recovery of high-purity silicon from the silicon cutting waste; when the melting time is greater than 30 min, the process energy consumption is too high.
[0059] Example
[0060] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0061] Example 1:
[0062] A method for recovering high-purity silicon from silicon crystal cutting waste includes the following preparation steps:
[0063] (1) Na2CO3, CaCO3, and binder are mixed into silicon cutting waste powder. The mass ratio of silicon cutting waste powder, Na2CO3, CaCO3, and distilled water is 400:50:10:4. At this time, SiO2, Na2CO3, and CaCO3 are mixed. During the mixing process, silicon cutting waste powder, Na2CO3 powder, and CaCO3 powder are added simultaneously and mixed in a double cone mixer for 20 minutes. Then, binder and distilled water are continuously sprayed from the nozzle of the mixer for 10 minutes.
[0064] (2) A mixture of silicon wafer cutting waste powder, Na2CO3 powder, CaCO3 powder, and distilled water was pressed into a green body. The upper surface pressure during pressing was 20 MPa, followed by vacuum drying to remove the distilled water from the green body. The green body after removing the distilled water was then subjected to spark plasma sintering (SPS) in a graphite crucible. The sintering atmosphere was argon, with an argon flow rate of 100 mL / min, a sintering temperature of 1300℃, and a holding time of 20 min. Na2CO3 and CaCO3 decomposed to form metal oxides and released CO2 gas. The metal oxides reacted with the surface layer of the SiO2 coating layer of the silicon wafer cutting waste to form a molten phase. More importantly, the CO2 released from the decomposition formed microbubbles in the molten phase. The impact effect of the microbubbles further accelerated the disintegration of the molten phase on the surface layer of the SiO2 coating layer.
[0065] (3) Further increase the power of the discharge plasma sintering furnace. At a furnace temperature of 1550℃, melt the sample after the SiO2 coating layer obtained in S2 as a whole. The melting time is 15 min, and the argon flow rate is the same as in (2). Due to the density difference of the melt, the Si melt composed of Si cores inside the silicon cutting waste and the oxide melt phase containing SiO2 molecules on the surface of the silicon cutting waste appear to separate. After cooling, the upper part of the graphite crucible is the oxide layer containing the SiO2 coating layer of the silicon cutting waste, and the lower part of the graphite crucible is the high-purity Si layer obtained by recycling.
[0066] Example 2:
[0067] A method for recovering high-purity silicon from silicon crystal cutting waste includes the following preparation steps:
[0068] (1) Na2CO3, CaCO3, and distilled water are mixed into the silicon cutting waste powder, with a mass ratio of 500:40:10:5. During the mixing process, the silicon cutting waste powder, Na2CO3 powder, and CaCO3 powder are added simultaneously and mixed in a double cone mixer for 20 minutes. Then, the binder distilled water is continuously sprayed from the nozzle of the mixer for 10 minutes.
[0069] (2) A mixture of silicon wafer cutting waste powder, Na2CO3 powder, CaCO3 powder, and distilled water was pressed into a green body. The pressure on the upper surface during pressing was 20 MPa, followed by vacuum drying to remove the distilled water from the green body. The green body after removing the distilled water was then subjected to spark plasma sintering (SPS) in a graphite crucible. The sintering atmosphere was argon, with an argon flow rate of 120 mL / min, a sintering temperature of 1350 °C, and a holding time of 25 min. Na2CO3 and CaCO3 decomposed to form metal oxides and released CO2 gas. The metal oxides reacted with the surface layer of the SiO2 coating layer of the silicon wafer cutting waste to form a molten phase. More importantly, the CO2 released from the decomposition formed microbubbles in the molten phase. The impact effect of the microbubbles further accelerated the disintegration of the molten phase on the surface layer of the SiO2 coating layer.
[0070] (3) Further increase the power of the discharge plasma sintering furnace. At a furnace temperature of 1570℃, melt the sample after the SiO2 coating layer obtained in S2 as a whole. The melting time is 20 min, and the argon flow rate is the same as in (2). Due to the density difference of the melt, the Si melt composed of Si cores inside the silicon cutting waste and the oxide melt phase containing SiO2 molecules on the surface of the silicon cutting waste appear to separate. After cooling, the upper part of the graphite crucible is the oxide layer containing the SiO2 coating layer of the silicon cutting waste, and the lower part of the graphite crucible is the high-purity Si layer obtained by recycling.
[0071] Example 3:
[0072] A method for recovering high-purity silicon from silicon crystal cutting waste includes the following preparation steps:
[0073] (1) Na2CO3, CaCO3, and distilled water are mixed into silicon cutting waste powder, with a mass ratio of 600:30:10:4. During the mixing process, silicon cutting waste powder, Na2CO3 powder, and CaCO3 powder are added simultaneously and mixed in a double cone mixer for 20 minutes. Then, distilled water as a binder is continuously sprayed from the nozzle of the mixer for 10 minutes.
[0074] (2) A mixture of silicon wafer cutting waste powder, Na2CO3 powder, CaCO3 powder, and distilled water was pressed into a green body. The upper surface pressure during pressing was 20 MPa, followed by vacuum drying to remove the distilled water from the green body. The green body after removing the distilled water was then subjected to spark plasma sintering (SPS) in a graphite crucible. The sintering atmosphere was argon, with an argon flow rate of 100 mL / min, a sintering temperature of 1300℃, and a holding time of 20 min. Na2CO3 and CaCO3 decomposed to form metal oxides and released CO2 gas. The metal oxides reacted with the surface layer of the SiO2 coating layer of the silicon wafer cutting waste to form a molten phase. More importantly, the CO2 released from the decomposition formed microbubbles in the molten phase. The impact effect of the microbubbles further accelerated the disintegration of the molten phase on the surface layer of the SiO2 coating layer.
[0075] (3) Further increase the power of the discharge plasma sintering furnace. At a furnace temperature of 1550℃, melt the sample after the SiO2 coating layer obtained in S2 as a whole. The melting time is 15 min, and the argon flow rate is the same as in (2). Due to the density difference of the melt, the Si melt composed of Si cores inside the silicon cutting waste and the oxide melt phase containing SiO2 molecules on the surface of the silicon cutting waste appear to separate. After cooling, the upper part of the graphite crucible is the oxide layer containing the SiO2 coating layer of the silicon cutting waste, and the lower part of the graphite crucible is the high-purity Si layer obtained by recycling.
[0076] Example 4:
[0077] A method for recovering high-purity silicon from silicon crystalline cutting waste includes the following preparation steps:
[0078] (1) Na2CO3, CaCO3, and distilled water are mixed into silicon cutting waste powder. The mass ratio of silicon cutting waste powder, Na2CO3, CaCO3, and distilled water is 700:20:10:4. At this time, SiO2, Na2CO3, and CaCO3 are mixed. During the mixing process, silicon cutting waste powder, Na2CO3 powder, and CaCO3 powder are added simultaneously and mixed in a double cone mixer for 20 minutes. Then, distilled water as a binder is continuously sprayed from the nozzle of the mixer for 10 minutes.
[0079] (2) A mixture of silicon wafer cutting waste powder, Na2CO3 powder, CaCO3 powder, and distilled water was pressed into a green body. The pressure on the upper surface during pressing was 20 MPa, followed by vacuum drying to remove the distilled water from the green body. The green body after removing the distilled water was then subjected to spark plasma sintering (SPS) in a graphite crucible at a heating rate of 225 °C / min, an argon atmosphere with an argon flow rate of 100 mL / min, a sintering temperature of 1300 °C, and a holding time of 20 min. Na2CO3 and CaCO3 decomposed to form metal oxides and released CO2 gas. The metal oxides reacted with the surface layer of the SiO2 coating layer of the silicon wafer cutting waste to form a molten phase. The time difference between the release of CO2 gas and the formation of the molten phase was approximately 2 minutes. More importantly, the CO2 released from the decomposition formed microbubbles in the molten phase. The impact effect of the microbubbles further accelerated the disintegration of the SiO2 coating layer surface layer by the molten phase.
[0080] (3) Further increase the power of the discharge plasma sintering furnace. At a furnace temperature of 1550℃, melt the sample after the SiO2 coating layer obtained in S2 as a whole. The melting time is 15 min, and the argon flow rate is the same as in (2). Due to the density difference of the melt, the Si melt composed of Si cores inside the silicon cutting waste and the oxide melt phase containing SiO2 molecules on the surface of the silicon cutting waste appear to separate. After cooling, the upper part of the graphite crucible is the oxide layer containing the SiO2 coating layer of the silicon cutting waste, and the lower part of the graphite crucible is the high-purity Si layer obtained by recycling.
[0081] Comparative Example 1:
[0082] A method for digesting the SiO2 coating layer of silicon cutting waste and recovering high-purity silicon (CaO powder and distilled water are used as binders).
[0083] (1) Na2CO3, CaO, and distilled water are mixed into silicon cutting waste powder, with a mass ratio of silicon cutting waste powder, Na2CO3, CaO, and distilled water of 700:20:10:4. During the mixing process, silicon cutting waste powder, Na2CO3 powder, and CaO powder are added simultaneously and mixed in a double cone mixer for 20 minutes; then, distilled water as a binder is continuously sprayed from the nozzle of the mixer for 10 minutes.
[0084] (2) A mixture of silicon wafer cutting waste powder, Na2CO3 powder, CaO powder, and distilled water was pressed into a green body. The pressure on the upper surface during pressing was 20 MPa, followed by vacuum drying to remove the distilled water from the green body. The green body after removing the distilled water was then subjected to spark plasma sintering (SPS) in a graphite crucible. The sintering atmosphere was argon, with an argon flow rate of 100 mL / min, a sintering temperature of 1300℃, and a holding time of 20 min. Only Na2CO3 decomposed to form Na2O and released CO2 gas, while CaO reacted with distilled water to form calcium hydroxide and became ineffective. Na2O reacted with the surface layer of the SiO2 coating layer of the silicon wafer cutting waste to form a molten phase. Only a small amount of CO2 formed microbubbles in the molten phase, which was insufficient to accelerate the dissolution of the SiO2 coating layer surface.
[0085] (3) Further increase the power of the discharge plasma sintering furnace. At a furnace temperature of 1550℃, melt the entire sample obtained in S2 for 15 minutes. The argon flow rate is the same as in (2). Due to the small amount of molten phase generated, the Si melt composed of Si cores inside the silicon crystalline silicon cutting waste and the oxide molten phase containing SiO2 molecules on the surface of the silicon crystalline silicon waste are not clearly separated. The high-purity Si layer recovered from the bottom of the graphite crucible is relatively thin.
[0086] Comparative Example 2:
[0087] A method for digesting the SiO2 coating layer of silicon cutting waste and recovering high-purity silicon (CaO powder, anhydrous ethanol as binder).
[0088] (1) Na2CO3, CaO, and anhydrous ethanol were mixed into silicon cutting waste powder, with a mass ratio of 700:20:10:4. During the mixing process, silicon cutting waste powder, Na2CO3 powder, and CaO powder were added simultaneously and mixed in a double cone mixer for 20 minutes. Then, anhydrous ethanol as a binder was continuously sprayed into the mixer nozzle for 10 minutes.
[0089] (2) A mixture of silicon wafer cutting waste powder, Na2CO3 powder, CaO powder, and anhydrous ethanol was pressed into a green body. The pressure on the upper surface during pressing was 20 MPa, followed by vacuum drying to remove the anhydrous ethanol from the green body. The green body after removing the anhydrous ethanol was then subjected to spark plasma sintering (SPS) in a graphite crucible. The sintering atmosphere was argon, the argon flow rate was 100 mL / min, the sintering temperature was 1300℃, and the holding time was 20 min. Only Na2CO3 decomposed to form Na2O and released CO2 gas. CaO was not degraded (as in the comparative example), but it also did not have the ability to decompose and produce CO2 gas. Na2O and CaO reacted with the surface layer of the SiO2 coating layer of the silicon wafer cutting waste to form a molten phase. Only a small amount of CO2 formed microbubbles in the molten phase, which was insufficient to accelerate the dissolution of the SiO2 coating layer surface layer.
[0090] (3) Further increase the power of the discharge plasma sintering furnace. At a furnace temperature of 1550℃, melt the entire sample obtained in S2 for 15 minutes. The argon flow rate is the same as in (2). Due to the small amount of molten phase generated, the Si melt composed of Si cores inside the silicon crystalline silicon cutting waste and the oxide molten phase containing SiO2 molecules on the surface of the silicon crystalline silicon waste are not clearly separated. The high-purity Si layer recovered from the bottom of the graphite crucible is relatively thin.
[0091] In Examples 1, 3, and 4, the mass fractions of silicon wafer cutting waste powder, Na₂CO₃, and CaCO₃ differ, while all other conditions remain the same. (Refer to the accompanying drawings.) Figure 2 and Figure 3 It can be seen that the amount of CO2 gas phase generated during the digestion of the SiO2 coating layer in Examples 1, 3, and 4 decreases sequentially, which leads to a sequential decrease in the concentration of CO2 microbubbles in the molten phase. Therefore, the rate of SiO2 coating layer digestion decreases sequentially in Examples 1, 3, and 4. This ultimately results in a sequential decrease in the high-purity silicon recovery rate in Examples 1, 3, and 4, under the same holding time. The test results of the above products demonstrate the effectiveness of CO2 microbubbles in the molten phase in accelerating the digestion of the SiO2 coating layer. Figure 2 When the amount of Na2CO3 and CaCO3 added is located in the shaded area in the figure, the SiO2 layer on the surface of the silicon crystalline cutting waste will be completely dissolved into the molten phase.
[0092] In Example 4 (CaCO3 powder, with distilled water as binder), Comparative Example 1 (CaO powder, with distilled water as binder), and Comparative Example 2 (CaO powder, with anhydrous ethanol as binder), the digestion temperature, digestion time, melting temperature, and melting time were all consistent. The silicon recovery rate in Example 4 was significantly higher than that in Comparative Example 1. This verifies the significant advantages of CaCO3 over CaO in avoiding reaction with water and in generating CO2 microbubbles to accelerate the digestion of the SiO2 coating layer. In Comparative Example 2, anhydrous ethanol was used as the binder to avoid CaO deactivation, but the silicon recovery rate was still significantly lower than that in Example 4. This further verifies the effect of CO2 microbubbles in accelerating the digestion of the SiO2 coating layer in Example 4.
[0093] Regarding the further control of the heating rate and the time difference between carbon dioxide release and molten phase formation in Example 4, by strictly controlling the carbon dioxide formation time, as much CO2 gas phase as possible is generated in the molten phase, forming more CO2 microbubbles, so that more CO2 microbubbles can play a role in accelerating the dissolution of the SiO2 layer on the surface of the silicon cutting waste by the molten phase. If the heating rate is too small, the molten phase will not be formed after the carbon dioxide is generated, and the formed carbon dioxide cannot enter the molten phase and cannot play a role in dissolving the SiO2 layer on the surface of the silicon cutting waste. If the heating rate is too fast, the amount of carbon dioxide released when the molten phase is formed will be small, and it will not play a good role in accelerating the dissolution of the SiO2 layer on the surface of the silicon cutting waste.
[0094] The recovery rates of high-purity Si in Examples 1-4 and Comparative Examples 1-2 are shown in Table 1.
[0095] Table 1
[0096] Silicon recovery rate % 85 83 80 74 46 52
[0097] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. A method for recovering high-purity silicon from silicon crystal cutting waste, characterized in that, Includes the following steps: S1. A small amount of carbonate and distilled water are mixed into the silicon cutting waste powder to obtain a homogeneous mixture of silicon cutting waste powder, carbonate, and binder; the carbonate is CaCO3 and Na2CO3; wherein the mass ratio of silicon cutting waste, Na2CO3, CaCO3, and binder is 300-800:10-60:10:4-8, and the amount of CaCO3 and Na2CO3 added is selected from the region of the SiO2-CaCO3-Na2CO3 ternary phase diagram that contains only the molten phase and gas phase and no solid phase; S2. After pressing the mixture of silicon cutting waste powder, carbonate powder, and binder into a blank, vacuum drying is performed to remove the binder from the blank. Then, spark plasma sintering is carried out in a graphite crucible. The sintering atmosphere is argon, the sintering temperature is 1300℃-1450℃, and the holding time is 20-40 min. During the sintering process, Na2CO3 and CaCO3 thermally decompose to generate Na2O and CaO and release CO2 gas. Na2O and CaO react with the SiO2 coating layer on the surface of the silicon cutting waste to form a molten phase. At the same time, the CO2 released by decomposition forms microbubbles in the molten phase to accelerate the dissolution of the SiO2 coating layer by the molten phase. S3. Increase the power of the discharge plasma sintering furnace to achieve a furnace temperature of 1550-1650℃ and melt for 15-30 minutes. Utilize the density difference to cause the Si melt composed of Si cores inside the silicon cutting waste to separate into layers with the oxide melt phase containing SiO2 molecules. After cooling, the high-purity Si layer obtained from the bottom of the graphite crucible is recovered.
2. The method for recovering high-purity silicon from silicon crystal cutting waste according to claim 1, characterized in that, The adhesive mentioned in step S1 is at least one of distilled water and anhydrous ethanol.
3. The method for recovering high-purity silicon from silicon crystal cutting waste according to claim 1, characterized in that, In step S1, silicon cutting waste powder, Na2CO3 powder, and CaCO3 powder are added simultaneously and mixed in a double cone mixer for 15-25 minutes; then, binder is continuously sprayed from the nozzle of the mixer for 6-15 minutes.
4. A method for recovering high-purity silicon from silicon crystal cutting waste according to claim 1, characterized in that, In step S2, when pressing the billet, a pressure of 18-25 MPa is applied to the upper surface of the billet.
5. The method for recovering high-purity silicon from silicon crystal cutting waste according to claim 1, characterized in that, In step S2, the sintering atmosphere is argon atmosphere, and the argon flow rate is 100-200 mL / min.
Citation Information
Patent Citations
Method for recovering silicon material from waste materials in cutting crystalline silicon by diamond wire
CN102642835A
Comprehensive treatment method for monocrystalline silicon / polycrystalline silicon cutting waste
CN111196696A
Boron-removing purification method of polysilicon
CN101671023A
Mixed material, melting method, metallic silicon and recycling method thereof
CN109704343A
